Application Of The Active Force Control Method To Reduce The Vibration Of The Suspended Handle - Rogaizat, Farah Naimah (Universiti Sains Malaysia, 2017)
In this study, active vibration control (AVC) methods with two types of controllers are applied to attenuate the vibration of the available suspended handle experimentally. The vibration is simulated to the suspended handle using shaker and the vibration measurement is taken using two accelerometers, whereby one is placed at the actuator location and another one at the handle of the suspended handle. Piezoelectric actuator is used to counter the vibration of the suspended handle that excited by the shaker. Two types of controllers are used in this study, which is Proportional-integral-derivative (PID) and Active Force Control (AFC). The result shows that, the PID controller can reduced the vibration (i.e., acceleration) up to 42.56 % at the actuator location and 39.78 % at the handle location, respectively. When AFC is included to the system, the vibration is further reduced up to 38.35 % at the actuator location and 36.95 % at the handle location, respectively. This result proved that, by using PID-AFC controller, the vibration reduction of the suspended handle can be further improved and this controller can be applied to reduce the vibration of the hand-held power tool in a daily application.